(untitled) (Brazilian Journal of Health Research, 2022)
Introduction: Airway obstruction by a foreign body in children usually occurs in the preschool phase, caused by food or toys. This condition must be identified and reversed quickly to avoid sequelae. Therefore, teachers and guardians must know the techniques for clearing the airways. Objective: to evaluate the knowledge of pre-school teachers about airway clearance techniques. Methods: This is a cross-sectional study, carried out in May 2019, in 8 public schools in a municipality in Ceará. Sociodemographic, academic training and knowledge assessment information was collected on the identification of airway obstruction and how to perform it as unblocking maneuvers. Results were obtained using descriptive statistics and all ethical principles were respected (Approval nº 3,313,385). Results: 58 teachers participated in the study. They were female (100%), hired for a limited period (58.6%), with an average professional performance of 5.19 (± 4.88) years. The average of correct answers was 8.36 (± 2.0) questions. The conduct that received the most hits was about the direction in which the compressions should be applied (69%), whereas the conduct that received the least hits was about the first action to be taken when a child does not cough or has an ineffective cough (36.2 %). Conclusion: the necessary dissipating teachers on the airway clearance techniques, however, there is still a deficiency in the attitude to be there after the identification of the main signs of obstruction and the correct practice of clearing maneuvers.